2018
DOI: 10.4014/jmb.1812.02044
|View full text |Cite
|
Sign up to set email alerts
|

Decursin and Z-Ligustilide in Angelica tenuissima Root Extract Fermented by Aspergillus oryzae Display Anti-Pigment Activity in Melanoma Cells

Abstract: The anti-melanogenic effects of the extract of Angelica tenuissima (AT) root and the extract of AT root fermented by Aspergillus oryzae (FAT) were investigated. These effects were determined by measuring the inhibitory activity of AT and FAT on melanin production in B16F10 melanocytes and with in vitro tyrosinase activity assays. The AT extract inhibited melanin production at concentrations above 250 μg/ml, and this inhibitory effect was significantly enhanced by the fermentation process with A. oryzae. HPLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition, J3 showed considerable potential for converting glucose to pivotal intermediates, such as acetate, ethanol, pyruvate, and acetyl-coA, which might then serve as direct or indirect substrates for JF flavor compounds including ethyl acetate, ethyl butanoate, ethyl propanoate, ethyl 2-hydroxypropanoate, ethyl 2-hydroxyhexanoate, acetic acid, 2-acetylpyridine, hexyl acetate, benzyl acetate ethyl, ethyl 3-methylbutanoate, ethyl benzeneacetate, and 3-methylbutyl acetate (Fan et al, 2012; Wang et al, 2014; Xiao et al, 2016; Gao et al, 2017). The highly expressed enzymes related to glycolysis and pyruvate metabolism were mostly derived from fungal species, some of which have been applied to the production of fermented foods and drugs, such as A. fumigatus (Qin et al, 2012; Wakefield et al, 2017), A. clavatus (Mo et al, 2008; Zutz et al, 2013; Li et al, 2017), and A. oryzae (Park et al, 2018; Son et al, 2018; Zhong et al, 2018). Furthermore, low concentration of ethanol might be generated by several fungi in J3, which to some extent agreed with the earlier finding that a small amount of ethanol could be directly produced by co-culture of fungi (Takano and Hoshino, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, J3 showed considerable potential for converting glucose to pivotal intermediates, such as acetate, ethanol, pyruvate, and acetyl-coA, which might then serve as direct or indirect substrates for JF flavor compounds including ethyl acetate, ethyl butanoate, ethyl propanoate, ethyl 2-hydroxypropanoate, ethyl 2-hydroxyhexanoate, acetic acid, 2-acetylpyridine, hexyl acetate, benzyl acetate ethyl, ethyl 3-methylbutanoate, ethyl benzeneacetate, and 3-methylbutyl acetate (Fan et al, 2012; Wang et al, 2014; Xiao et al, 2016; Gao et al, 2017). The highly expressed enzymes related to glycolysis and pyruvate metabolism were mostly derived from fungal species, some of which have been applied to the production of fermented foods and drugs, such as A. fumigatus (Qin et al, 2012; Wakefield et al, 2017), A. clavatus (Mo et al, 2008; Zutz et al, 2013; Li et al, 2017), and A. oryzae (Park et al, 2018; Son et al, 2018; Zhong et al, 2018). Furthermore, low concentration of ethanol might be generated by several fungi in J3, which to some extent agreed with the earlier finding that a small amount of ethanol could be directly produced by co-culture of fungi (Takano and Hoshino, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, other compounds are not reported about their skin wound healing- or melanogenesis-linked bioactivities on keratinocytes and melanocytes. Angelica dahurica extract increased human keratinocyte proliferation [ 10 ] and Angelica tenuissima root extract inhibited melanin production in melanoma cells [ 11 ]. In the present study, we found that APMFAb promoted skin wound healing and whitening response.…”
Section: Resultsmentioning
confidence: 99%
“…(APM; family Umbelliferae ) is distributed in Korea, China, Japan, and New Zealand [ 8 ], and its roots are used in traditional medicine to treat or relieve chronic gastritis, stomach aches, rheumatic pain, gastric ulcers, and duodenal bulbar ulcers [ 9 ]. It has been reported that extracts of Angelina species have the ability to induce proliferation of keratinocytes or inhibit melanin synthesis in melanocytes [ 10 , 11 ]. APM root extract and bisabolangelone, a compound found in its root extract, have been known to have anti-ulcer effects in vivo [ 9 ] and inhibit the activities of human SH-SY5Y neuroblastoma cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have corroborated that ligustilide exerts broad pharmaceutical applications in various diseases, such as cardiovascular disease, 15 brain injury, and inflammation. 16 Increasing evidence reveals the critical roles of ligustilide in the progression of several carcinomas, including ovarian cancer, 17 breast cancer, 18 melanoma, 19 and glioma. 20 For instance, administration with ligustilide restrains the migration of glioma cells.…”
Section: Impact Statementmentioning
confidence: 99%